2006
DOI: 10.1093/hmg/ddl005
|View full text |Cite
|
Sign up to set email alerts
|

Generation of trans-mitochondrial mice carrying homoplasmic mtDNAs with a missense mutation in a structural gene using ES cells

Abstract: Generation of various kinds of trans-mitochondrial mice, mito-mice, each carrying mtDNAs with a different pathogenic mutation, is required for precise investigation of the pathogenesis of mitochondrial diseases. This study used two respiration-deficient mouse cell lines as donors of mtDNAs with possible pathogenic mutations. One cell line expressed 45-50% respiratory activity due to mouse mtDNAs with a T6589C missense mutation in the COI gene (T6589C mtDNA) and the other expressed 40% respiratory activity due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 35 publications
5
71
0
1
Order By: Relevance
“…Our previous study (19) also showed that young mito-miceND6 M (3-mo-old males) have slight lactic acidosis, a common phenotype in humans with mitochondrial diseases (1, 2) and in mito-mice with other pathogenic mtDNA mutations (20)(21)(22). Using aged mitomiceND6 M (21-mo-old males), this study reexamined blood lactate levels.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Our previous study (19) also showed that young mito-miceND6 M (3-mo-old males) have slight lactic acidosis, a common phenotype in humans with mitochondrial diseases (1, 2) and in mito-mice with other pathogenic mtDNA mutations (20)(21)(22). Using aged mitomiceND6 M (21-mo-old males), this study reexamined blood lactate levels.…”
Section: Resultsmentioning
confidence: 83%
“…Using aged mitomiceND6 M (21-mo-old males), this study reexamined blood lactate levels. We also used mito-miceCOI M , which we had generated previously (21), as positive controls with lactic acidosis due to respiration complex IV defects caused by a pathogenic T6589C mtDNA mutation in the COI gene. Unlike B6 mice, both aged mito-miceND6 M and age-matched mito-miceCOI M (21-mo-old males) had slight lactic acidosis in the peripheral blood (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported previously that mtDNA-induced respiration defects expressed in cultivated P29 cybrids can be restored when the pathogenic mtDNAs are transferred into mouse tissues [7,23]. This restoration is presumed to be a consequence of some compensatory function that is exclusively present in the tissues but not in cultivated P29 cybrids.…”
Section: Discussionmentioning
confidence: 97%
“…This restoration is presumed to be a consequence of some compensatory function that is exclusively present in the tissues but not in cultivated P29 cybrids. For example, P29mtA11 and P29mt6589 cybrids, which possess a G13997A mutation in the mtNd6 gene and a T6589C mutation in the mt-Co1 gene, show approximately 20% complex I [3] and 40% complex IV activity [7], respectively, when compared with P29mtB6 cybrids. In contrast, tissues from the transmitochondrial mice, mito-mice13997 and mito-mice6589, which in turn possess G13997A and T6589C mtDNA introduced from the P29mtA11 and P29mt6589 cybrids, show approximately 70% complex I [23] and 70% com- plex IV activity [7], respectively, when compared with age-matched B6 mice.…”
Section: Discussionmentioning
confidence: 99%